PENERAPAN TPS DALAM PEMBELAJARAN TARI DI SMA N 12 BANDAR LAMPUNG - Eka Putrika Mutia; Fitri Daryanti; Hasyimkan Hasyimkan (Jurnal Seni dan Pembelajaran, 2014)
This research aims to describe how to implementation of Cooperatif Learning. Model TPS and the learning outcome of Bedana dance lessons learned in extracurricular activities in SMAN 12 Bandar Lampung. this research used a qualitative descriptive method. Technique that used to collect the data are observation, interview, field notes, documentation, tes of dance and non test. Based on qualitative analisis of the observasion sheets from the achievement of cooperative learning using TPS type can be seen 1)think, students is categorized as very good (85). 2) pair, students is categorized as very good (80). 3) share, students is kategorized as very good (100). For the observation individual practice tests sheets 1 and 2, can be seen the average value that gets by all of students is categorized as very good (82). But from the students activities can be seen the average value as a good criteria (85). Penelitian ini bertujuan mendeskripsikan bagaimanakah penerapan model kooperatif tipe TPS dan bagaimanakah hasil pembelajaran tari Bedana pada kegiatan Ekstrakurikuler di SMA N 12 Bandar Lampung. Metode penelitian yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, catatan lapangan, dokumentasi, tes praktik dan non tes. Hasil pengamatan pencapaian proses pembelajaran menggunakan model kooperatif tipe TPS dapat diketahui bahwa 1) Think, siswa tergolong kriteria baik sekali (85). 2) Pair, siswa tergolong kriteria baik sekali (80). 3) Share, siswa tergolong kriteria baik sekali (100). Untuk hasil lembar pengamatan tes praktik individu 1 dan 2, dapat diketahui rata-rata nilai yang didapat seluruh siswa tergolong dalam kriteria baik sekali (82). Sedangkan ditinjau dari aktivitas siswa didapat kriteria baik sekali (85). Kata kunci: pembelajaran, tari Bedana, TPS.